2021
DOI: 10.1002/pbc.28983
|View full text |Cite
|
Sign up to set email alerts
|

Drug penetration in pediatric brain tumors: Challenges and opportunities

Abstract: Larger clinical trial enrollments and a greater understanding of biological heterogeneity have led to improved survival rates for children diagnosed with brain tumors in the last 50 years. However, reducing long‐term morbidities and improving survival rates of high‐risk tumors remain major challenges. Chemotherapy can reduce tumor burden, but effective drug penetration at the tumor site is limited by barriers in the route of drug administration and within the tumor microenvironment. Bioavailability of drugs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 230 publications
(289 reference statements)
0
8
0
Order By: Relevance
“…Over the past century, we have made strides in developinng chemotheraputic drugs. However, there remains a gap in having the pre-clinical cytotoxic sucesses translate to patient survival [3, 19]. Through this pilot experiment compairing the distribution of DOX susposended in solution and DOX loaded into a a 10% starch hydrogel we have shown that this testing platform allows for the monitoring of diffusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past century, we have made strides in developinng chemotheraputic drugs. However, there remains a gap in having the pre-clinical cytotoxic sucesses translate to patient survival [3, 19]. Through this pilot experiment compairing the distribution of DOX susposended in solution and DOX loaded into a a 10% starch hydrogel we have shown that this testing platform allows for the monitoring of diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Among childhood cancer survivors, 99% develop chronic conditions from the toxicity of the chemotherapy used to treat their initial malignancy [1][2][3][4]. These chronic conditions can be severe, disabling, or even life-threatening and can manifest years after completion of therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotherapies administered orally and intravenously are part of the standard of care treatment for most pediatric tumors, with pediatric patients diagnosed with medulloblastoma treated with mostly, if not only, chemotherapy [2][3][4]. Sadly, barriers to the systemic route of administration limit drug penetration in the tumor microenvironment and include but are not limited to plasma protein binding, the blood-brain barrier, and structural and mechanical components within the tumor microenvironment all hindering the potential of therapeutic effect on the cancer cells [5][6][7][8]. In treating brain tumors, nearly 98% of small molecules and 100% of large molecules do not cross the blood-brain barrier, defining the blood-brain barrier as the most significant physical obstacle to treating brain tumors [9,10].…”
Section: Introductionmentioning
confidence: 99%